Features graphic design in the development of packaging design (Herald of Journalism, 2020)
The purpose of this article is to focus on graphic design and packaging design methods around the world. Wrapping packaging is one of the means of communication with a potential consumer who can choose goods based on packaging of goods. There are also special types of packaging of goods depending on the purpose: consumer, transport, external and internal. In addition, it is important to adhere to  the principle of compliance. The method of packaging the product must comply with its specifications and delivery conditions. Also, some types of food traditionally require the use of certain colors. For ex- ample: dairy products – white, green and blue, the colors of lush grass or sky; baked products – yellow, sandy or brown. One of the important aspects when promoting a product on the market is the color of the package, which is why some mixed shades (for example, light purple) by their nature can cause nega- tive associations and cast doubt on the production nature of the product.The research methods used in writing the article were studied the design of domestic and foreign packaging, requirements and materials for them. As a developing system, we consider the advertising table of packaging and analyze the principles of integrating the drawing, photographic, color and struc- tural structure of packaging using comparative analytical and stylistic analysis. In addition, during the work was studied a number of foreign web resources, providing technology for the production of pack- aging and its contemporary design: koloro.ua, www.toxel.com, www.bibliofond.ru practical significance  of the research is to understand the design of labels and labeling and to use the experience gained in modern design and art education.Leading global designers have come to the conclusion that packaging design can be viewed as a type of creative endeavor, not just mechanical work. Creatively designed packaging inspires the buyer  to purchase the product. There are many types of packaging for various purposes on the market. Among them, packaging from environmental and recycled materials, which can contribute to a clean environ- ment, which includes ponds, rivers, streams and other bodies of water, occupies a special position. There is an innovative type of packaging that can affect our daily lives.
Keywords: design, packaging-wrapping-encasing, product, consumption, design.